New ways of working practices - Leede, Jan de (Emerald Group Publishing Limited, 2016)
New technologies, new office concepts and new working environments are all big concepts, and we are just at the start of understanding the impact of these global trends on shaping our behaviors at work. This book describes and analyses the trends known as 'New Ways of Working' primarily addressing the behavioral side of NWW practices as many researchers and practitioners claim the success of NWW is not in IT, nor in facilities, but in behavior. We have to learn and to adapt to the new possibilities of collaboration at a distance. Our managers have to learn and to show new leadership behaviors in order to get the most out of it. And we have to learn how to build organizations that can easily absorb these new practices. Therefore, we present some new data on the use of NWW practices in the Dutch case as one of the leading countries in these global trends, concentrating on 4 HR-related themes: (1) trust, social cohesion and diversity, (2) leadership, (3) teamwork and (4) innovative work behavior. We show that NWW-practices entail much more than just home-based work or telework for a few people. It is changing everyone's work anytime, anyplace, anyhow.
Keywords: Telecommuting.; Flexible work arrangements.; elektronické knihy; electronic books